2004
DOI: 10.1634/stemcells.22-6-908
|View full text |Cite
|
Sign up to set email alerts
|

Fas Ligand as a Tool for Immunosuppression and Generation of Immune Tolerance

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 204 publications
(182 reference statements)
0
48
0
Order By: Relevance
“…37 In other studies Fas-L protein has been implemented in the reduction of allogenic rejection independent of apoptotic induction. 38,39 In our study, the Fas-L protein was upregulated by both the host and injected cells following transplantation, especially at day 10 when CD34 À cells were used. The distributions of Fas-L were found to be located in the nucleus and outer regions of the annulus, consistent with a previous report.…”
mentioning
confidence: 62%
“…37 In other studies Fas-L protein has been implemented in the reduction of allogenic rejection independent of apoptotic induction. 38,39 In our study, the Fas-L protein was upregulated by both the host and injected cells following transplantation, especially at day 10 when CD34 À cells were used. The distributions of Fas-L were found to be located in the nucleus and outer regions of the annulus, consistent with a previous report.…”
mentioning
confidence: 62%
“…In general, the role of FasL is potentially much more complex. For instance, experimental models of lung allogeneic grafts have indicated Fas ligand as a tool for immune suppression and tolerance [15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have clearly demonstrated the ability of FasL to protect allogeneic grafts from immune rejection and to sustain immune tolerance in an immune-privileged site such as the testis (23,24). Our results showed that the level of FasL was up-regulated from the first to the third weeks in vitro and at the second and third weeks in vivo during Sertoli cell infection with UU, while the control group values did not change.…”
Section: Discussionmentioning
confidence: 48%